THE ROLE OF BICS AND CALP IN THE INTEGRATION OF LANGUAGE AND CONTENT LEARNING IN THE PHYSICS LESSONS IN ENGLISH - Tastanov, M.G.; Kurmangaliyeva, А.А. (Publisher of Kostanay Regional University named after Akhmet Baityrsynuly, 2024)
The article discusses the importance of using the Quadrant Model to integrate linguistic and content skills in physics lessons. The Quadrant Model helps structure educational tasks, developing both Basic Interpersonal Communicative Skills (BICS) and Cognitive Academic Language Proficiency (CALP), ensuring a gradual transition from simple tasks with visual support to independent analysis of complex concepts. The article also provides recommendations for teachers on how to use the Quadrant Model to plan lessons and improve student performance in a bilingual environment.
Keywords: integration of BICS and CALP; bilingual education; physics in English; Quadrant Model; cognitive skills; language skills